2020
DOI: 10.1098/rspb.2020.2315
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary fine-tuning of background-matching camouflage among geographical populations in the sandy beach tiger beetle

Abstract: Background-matching camouflage is a widespread adaptation in animals; however, few studies have thoroughly examined its evolutionary process and consequences. The tiger beetle Chaetodera laetescripta exhibits pronounced variation in elytral colour pattern among sandy habitats of different colour in the Japanese Archipelago. In this study, we performed digital image analysis with avian vision modelling to demonstrate that elytral luminance, which is attributed to proportions of elytral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…We found significant differences in the ability to change dorsal colour and in background colour preferences between populations in Sardinia and Corsica. Although inter-individual and among-population differentiation in background matching abilities has been studied in other taxa (Marshall et al, 2015, 2016; Bailing et al, 2020; Yamamoto and Sota, 2020), including amphibians (Wente & Phillips, 2003; Kang et al, 2016; Barnett et al, 2021), this is the first study analysing patterns of variation in background matching abilities along a historical range expansion route. To the best of our knowledge, this is also the first study addressing spatial patterns of variation in anti-predatory traits in the context of the recent biogeographic history of populations.…”
Section: Discussionmentioning
confidence: 99%
“…We found significant differences in the ability to change dorsal colour and in background colour preferences between populations in Sardinia and Corsica. Although inter-individual and among-population differentiation in background matching abilities has been studied in other taxa (Marshall et al, 2015, 2016; Bailing et al, 2020; Yamamoto and Sota, 2020), including amphibians (Wente & Phillips, 2003; Kang et al, 2016; Barnett et al, 2021), this is the first study analysing patterns of variation in background matching abilities along a historical range expansion route. To the best of our knowledge, this is also the first study addressing spatial patterns of variation in anti-predatory traits in the context of the recent biogeographic history of populations.…”
Section: Discussionmentioning
confidence: 99%
“…Similar differential survival on matching and non‐matching backgrounds has been demonstrated in the tiger beetle Chaetodera laetescripta . Yamamoto and Sota ( 2020 ) found that there was a strong selective advantage for artificial beetle models that were placed on colour matching substrates, whereas the models on the non‐matching backgrounds suffered significantly higher predation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Yamamoto and Sota (2020) showed that natural selection by visual predators has driven the evolution of finely tuned background‐matching camouflage in the tiger beetle Chaetodera laetescripta . The elytral color of the beetle matches the background of local habitats (Yamamoto & Sota 2020). If selection leads to a correlation between body color and substrate in D. csikii , each type of sand in the different habitats would lead to a different body color of the crickets.…”
Section: Discussionmentioning
confidence: 99%
“…However, preference for cryptic substrate may have evolved in populations that inhabit narrower beaches or the edges of habitats because of greater opportunities for selection. In addition, Yamamoto and Sota (2020) showed that natural selection by visual predators has driven the evolution of finely tuned background‐matching camouflage in the tiger beetle Chaetodera laetescripta . The elytral color of the beetle matches the background of local habitats (Yamamoto & Sota 2020).…”
Section: Discussionmentioning
confidence: 99%